Knowledge gaps, lack of confidence, and system barriers to guideline implementation among European physicians managing patients with CIED lead or infection complications: a European Heart Rhythm Association/European Society of Cardiology educational needs assessment survey. Issue 11 (4th October 2020) - Rao, Archana; Garner, Daniel; Starck, Christoph; Kirkfeldt, Rikke Esberg; Dagres, Nikolaos; Didier, Klug; Montano, Nicolas; Heidbuchel, Hein
Abstract: As the number of patients with cardiac implantable electronic devices (CIEDs) grows, they are likely to present with issues to diverse groups of physicians. Guideline-adherent management is associated with improved prognosis in patients with CIED infection or lead problems but is insufficiently implemented in practice. The European Heart Rhythm Association (EHRA) with the support of the European Society of Cardiology (ESC) Working Group on Cardiovascular Surgery, performed a multinational educational needs assessment study in ESC member countries, directed at physicians who might be confronted with CIED patients with complications. A total of 336 physicians from 43 countries, reached through the ESC mailing list, participated. They included a mix of electrophysiologists, cardiologists general physicians and cardiac surgeons .One hundred and twenty-nine (38%) of the respondents performed lead extraction. The survey included eight clinical cases and a self-evaluation question of knowledge and skills to apply that knowledge. The survey looked at 14 areas of care across five stages of the patient journey. Of the non-extracting physicians over 50% felt they lacked the knowledge and skills to make the diagnosis and refer for lead extraction and over 75% felt they lacked knowledge and skills to manage aspects of extraction and post-extraction care. Barriers to correct referral were logistic and attitudinal. Extracting physicians reported significantly higher rates of adequate skills and knowledge across all five stages of the patient journey ( P < 0.05). We identified major gaps in physicians' knowledge and skills across all stages of CIED care. These gaps should be addressed by targeted educational activities and streamlining referral pathways.